A first case report of dapsone inducing recurrent ventricular arrhythmia. Issue 4 (20th September 2019) - Wong, Bethany; Saiva, Lavanya; Buckley, John; Galvin, Joseph
Abstract: Background: Ventricular arrhythmias (VAs) are life-threatening arrhythmias which are associated with significant morbidity and mortality. Ventricular arrhythmias are induced by a change in the myocardial environment altering cardiomyocyte electrophysiology. The substrate for VA includes myocardial scar, electrolyte disturbances, and drugs altering cellular electrophysiology. Case summary: Here, we present a case of a 52-year-old man with known ischaemic cardiomyopathy, presenting with VA storms secondary to dapsone, an anti-microbial used in this case for the prophylaxis of pneumocystis pneumonia. This is the first case linking dapsone to the development of VAs. Ventricular arrhythmias storm occurred towards the end of the course of anti-microbial therapy and the patient was referred for sympathectomy. However, following the end of treatment, no further VA occurred and sympathectomy was therefore avoided. Discussion: The underlying mechanism for the association between dapsone treatment and VA is unclear and a prolonged QTc was not observed in our case. It is important to recognize that every drug has many physiological effects and in patients with underlying diseases whereby there is already an unfavourable environment, additional drugs can lower the threshold of triggering an arrhythmia and the result can be life-threatening. In a patient with ischaemic cardiomyopathy, where underlying substrate for VA may already exist, the introduction of dapsone could lower the threshold for development of arrhythmia.